Shaping Science for Increasing Interdependence and Specialization. Issue 3 (March 2017) - Utzerath, Christian; Fernández, Guillén
Abstract : Like art, science affords an individualistic career. However, increasingly, complexity necessitates increased interdependency and specialization. Despite this change, many institutions, funding agencies, and publishers insist on an exclusively individualistic model of science. This hinders scientific progress by imposing a range of inefficiencies in the planning and execution of research plans.